Climate-literate graduates: A cross-sectional study assessing the integration of climate change education across university disciplines. - Mbanjwa, Sibonelo Thanda (Student's Journal of Health Research Africa, 2025)
Background The growing threat of climate change demands that higher education institutions equip students with the knowledge and skills to respond effectively. Yet, the extent and manner in which climate change education (CCE) is integrated into university curricula, particularly in Global South contexts like South Africa, remains underexplored. This study examined the integration of CCE within South African universities, identifying patterns, challenges, and opportunities for improvement. Methods A cross-sectional survey design targeted academic staff and final-year students across five faculties (Science, Engineering, Humanities, Education, and Commerce) at three South African universities. Data collection involved structured questionnaires and semi-structured interviews. Quantitative data were analysed using descriptive statistics, while qualitative responses were thematically analysed to reveal curricular practices and perceived barriers. Results A total of 121 participants (12 academic staff and 109 final-year students) were included. CCE integration varied significantly across faculties. Science showed the highest inclusion of climate content (89%), followed by Engineering and Education. Commerce and Humanities reported limited engagement (33% and 29%). Most climate content appeared in elective rather than core modules. Interviews highlighted key barriers: limited institutional support, inadequate staff training, and weak interdisciplinary collaboration. Students expressed a strong demand for practical, action-oriented climate education across all disciplines. Conclusion CCE remains uneven and fragmented within South African universities, with structural, institutional, and pedagogical challenges impeding broader integration. This inconsistency risks undermining graduates’ ability to address climate-related challenges in diverse professional contexts. Recommendation Universities should establish institution-wide climate literacy frameworks embedding CCE across faculties. Interdisciplinary curriculum development, staff capacity-building, and collaboration with industry and civil society are essential to produce climate-literate graduates capable of advancing